Identification of a Notched Kernel Gene Associated with Pre-Harvest Sprouting Using Oryza glumaepatula Introgression Lines in Rice - , Sobrizal; Atsushi Yoshimura (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
Pre-harvest sprouting in rice is related to the lack of a normal dormancy level during seed development and maturation. The prominent effects of pre-harvest sprouting are lower yield due to harvest losses and end-product quality reduction. A single novel gene (nk2) for notched kernel was identified at backcross segregating population (BC4F2) of Oryza glumaepatula to Oryza sativa cv. Taichung 65 as recurrent parent. The nk2 gene was closely associated to pre-harvest sprouting character, and mapped on the long arm of chromosome 5 with 3.5 cM and 3.6 cM distance to G1103 and R521 RFLP markers, respectively. Key words : Notched kernel, pre-harvest sprouting, genetic map, rice